Analysis and design of an annular-array MPT for the efficient generation of omnidirectional shear-horizontal waves in plates. (20th May 2019) - Park, Chung Il; Seung, Hong Min; Lee, Jun Kyu; Kim, Yoon Young
Abstract: Despite the fact that omnidirectional shear-horizontal (SH) waves have recently received much attention, there is no systematic design method with which to develop the corresponding transducers with enhanced output and power concentration levels at a target frequency. Here, we propose a method which can be used to design an optimal annular-array magnetostrictive patch transducer (MPT) that fulfills the above-mentioned objectives. The proposed transducer consists of optimally configured multiple magnetostrictive patches, consistently placed permanent magnets, and toroid coils. For the design, the transducer output signals are theoretically predicted using Green's function of guided waves in a plate and the analysis results are then used to develop new high-power annular-array MPTs generating omnidirectional SH waves in a plate. The validity of the analysis and the effectiveness of the design method were confirmed with numerical simulations and pitch-catch wave experiments performed on an aluminum plate. In the experiments, the mode selectivity and omnidirectivity of the designed transducer were also checked. While the proposed method is mainly developed for MPTs, it should be equally useful for the design of similar annular-type piezoelectric and electromagnetic acoustic guided wave transducers.